2019
DOI: 10.1556/2006.8.2019.03
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between young adult Internet addicts, smokers, and healthy controls by the interaction between impulsivity and temporal lobe thickness

Abstract: Background and aims: Internet addiction is a non-substance-related addiction disorder with progressively growing prevalence. Internet addiction, like substance-related addictions, has been linked with high impulsivity, low inhibitory control, and poor decision-making abilities. Cortical thickness measurements and trait impulsivity have been shown to have a distinct relationship in addicts compared to healthy controls. Thus, we test whether the cortical correlates of trait impulsivity are different in Internet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 79 publications
3
17
0
3
Order By: Relevance
“…As there are no clear diagnostic criteria for the internet addiction it is highly recommended to measure excessive internet use with a continuous questionnaire [4]. We chose the problematic internet use questionnaire (PIUQ) because its structure tightly adheres to the proposed diagnostic criteria for internet addiction and was created based on the clinimetric and psychometric analysis of Young's internet addiction test independently validated by several groups and used in our previous published work [14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…As there are no clear diagnostic criteria for the internet addiction it is highly recommended to measure excessive internet use with a continuous questionnaire [4]. We chose the problematic internet use questionnaire (PIUQ) because its structure tightly adheres to the proposed diagnostic criteria for internet addiction and was created based on the clinimetric and psychometric analysis of Young's internet addiction test independently validated by several groups and used in our previous published work [14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…Although this technology has improved many aspects of our lives and it is now an essential part of the everyday routine including work, private life and social functioning, many studies have reported the misuse of the internet (problematic internet use, internet addiction; IA) as summarized in a recent meta-analysis [ 1 ]. The individual suffering from internet addiction may not be aware of it and it remains unrecognized by their relatives, friends and colleagues [ 2 ]. IA may be classified as a compulsive-impulsive spectrum disorder based on symptomatology, but it has been under considerable research, and not included in the recently published 5th edition of the Diagnostic and Statistical Manual DSM-V [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some authors [17,[24][25][26][27] point to factors such as the lack of sleep, hyperactivity, insecurity when driving, anxiety, depression, personality disorders, etc., associated to harmful behaviors such as in the use drugs including heroin, alcohol, cannabis, speed, etc., that although not linked to technologies, have been observed in the population who have a problematic use of mobile phones. Nevertheless, some research studies [28] suggest that there is a common factor among the addictive behaviors in the use of substances and the internet, the impulsivity which is manifested, among other aspects, by low academic performance or low levels of concentration, however, this cannot be extrapolated to an addictive use of the smartphone.…”
Section: Introductionmentioning
confidence: 99%